Analysis of Self-Consciousness Based on the Multi-theory Perspective - Ghoffar, Helmi (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2019)
This article aims to describe the concept of self-awareness analyzed from several theoretical perspectives. This analysis is intended to form a synthesis as a comprehensive definition including the essence, aspects and indicators of self-awareness. The method used is descriptive analysis of various theories with a literature review approach. The results of this analysis will serve as a basis in the preparation of instruments which are expected to have a high level of validity to measure aspects of self-awareness that are more comprehensive in accordance with the context and situation at the present time.